Harm Perceptions of Menthol and Nonmenthol Cigarettes Differ by Brand, Race/Ethnicity, and Gender in US Adult Smokers: Results from PATH Wave 1. Issue 4 (27th January 2018) - Cohn, Amy M; Rose, Shyanika W; Ilakkuvan, Vinu; Gray, Tiffany; Curry, Laurel; Villanti, Andrea C; Mays, Darren; Lindblom, Eric; Tercyak, Kenneth; Debnam, Charles; Mayo, Ashley; Perreras, Lexie
Abstract: Introduction: Harm perceptions of menthol cigarettes may contribute to their appeal and use. African-Americans, women, and younger smokers disproportionately use menthol cigarettes, and may misperceive harm of menthol cigarettes. Methods: Data were from Wave 1 of the Population Assessment of Tobacco and Health (PATH) Study. Weighted analyses of current adult smokers (18 and older) were used to estimate the correlates of menthol smoking among all cigarette brands and separately for the top three cigarette brands (Newport, Camel, and Marlboro). Adjusted models examined the main effect of menthol smoking on harm perceptions of one's own brand of cigarette and interactions with race/ethnicity, age, and gender. Results: Menthol cigarettes were used by nearly 40% of current smokers, although the prevalence of menthol smoking differed across the top three brands (94% Newport, 46% Camel, and 18% Marlboro). Among menthol smokers, 80% perceived their cigarette as equally harmful, 14% perceived their brand as more harmful, and 7% perceived their brand as less harmful. In adjusted models, menthol smokers were more likely than nonmenthol smokers to misperceive their own brand as more harmful than other brands (compared to no difference in harm). Race and gender emerged as moderators of the association between menthol brand preference and harm perceptions. Conclusions: In adjusted analyses, menthol smokers were more likely than nonmenthol smokers to perceive their brand as more harmful than other brands, with differences by sub-groups who disproportionately use menthol. Implications: Menthol cigarettes have been historically marketed with messages conveying lower harm than other cigarettes. Little is known about how contemporary adult menthol smokers perceive the harm of their usual brand, and potential differences by race, gender, and young adult versus older adult age group. After adjusting for other factors, menthol smokers were more likely than nonmenthol smokers to perceive their cigarette brand as more harmful than other brands. Further, the association between menthol smoking and harm perceptions differed by race and gender, but not by age group (young adult vs. older adult). This type of large-scale study identifies critical links between menthol smoking and harm perceptions among vulnerable smokers that will inform regulatory actions designed to decrease smoking-related harm.